The Influence of Public Awareness on Knowledge and Behavior of Littering in The Village of Beras Basah, North SumateraThe Influence of Public Awareness on Knowledge and Behavior of Littering in The Village of Beras Basah, North Sumatera - Nanda, Meutia; Br Sitepu, Rehuliana Ninta; Hasanah, Nurul; Sinaga, Shelly Shabina Putri; Hasibuan, Khairunnisa; Dalimunthe, Wirdah Sufa Zein (Universitas Teuku Umar, 2024)
Waste is a problem that has not been addressed, especially in Indonesia. From time to time, the amount of trash continues to fluctuate. According to data from the Ministry of Environment and Forestry, the national waste pile in 2021 will reach 26.39 tons. This number has decreased compared to 2020 when the total national waste is estimated to reach 33.16 tons. This research aims to determine the main source of this pollution, to identify problems related to environmental sanitation due to the accumulation of waste, as well as the impact on health in Beras Basah Village, Pangkalan Susu Langkat District, North Sumatra. The results of the research show that environmental sanitation in the Beras Basah sub-district, especially in the ward the majority of people with low education generally only reach junior high school level. This research method is quantitative research. The data used in this research is primary data taking data from questionnaires, interviews, and documentary observations. The subjects of this research were 53 respondents who were different from village officials such as the village head, Kipling, and the local community. The research location is in Beras Basah Village, Pangkalan Susu District, Langkat, North Sumatra. The situation in Beras Basah Village is still not good, because the majority of people in Beras Basah Village still throw rubbish in the river. The lack of government attention in Beras Basah Village means that many people still dump rubbish at sea, because there is no infrastructure from the Beras Basah village government, such as rubbish transport cars which cannot enter the Ward XI area, the distance between the house and the TPS is quite far, etc